Tax Insights from Latin American and Caribbean in the Context of COVID-19 - Obando , Roberto Ramos; Aguilar , Jeancarlo Andino (American Scientific Research Journal for Engineering, Technology, and Sciences, 2020)
Appearing in early 2020, the Covid-19 pandemic has forced Latin American and Caribbean (LAC) countries to implement tax measures to support taxpayers and sustain tax revenue through the outbreak. Policy makers need to assess the implementation of these measures and future policies while considering current issues such as lack of fiscal space, shortage of economic flows, rushing digitalization and falling tax morale in the region. This contribution covers the current scenario in LAC and provides tax insights to be considered as the region moves forward after the crisis.